The ε4 genotype of apolipoprotein E and white matter integrity in Alzheimer's disease. Issue 3 (23rd May 2013) - Kljajevic, Vanja; Meyer, Peter; Holzmann, Carsten; Dyrba, Martin; Kasper, Elisabeth; Bokde, Arun L.W.; Fellgiebel, Andreas; Meindl, Thomas; Hampel, Harald; Teipel, Stefan; ,
Abstract: Background: In this multicenter study, we investigated a possible association between the APOE ε4 allele and white matter (WM) integrity in Alzheimer's disease (AD) using diffusion tensor imaging (DTI). Methods: We analyzed fractional anisotropy (FA) and mean diffusivity (MD) as indices of WM integrity in 70 AD patients (35 APOE ε4 carriers, 35 noncarriers) and 56 healthy control (HC) subjects (28 APOE ε4 carriers, 28 noncarriers). APOE ε4 carriers and noncarriers were matched for age and gender within each diagnostic group. Results: We found significant effects of diagnosis ( P corrected < .05 [FWE]; i.e., smaller FA values and larger MD values in AD patients compared with HCs) and significant effects ( P < .001) of APOE ε4 carrier status on MD in HCs but not in AD subjects. Conclusions: The results indicate that APOE ε4 has a moderate effect on WM integrity in HCs, but no effect on WM integrity in manifest AD.